Analisa Faktor Yang Berpengaruh Terhadap Nilai Perusahaan Dengan Kualitas Laba Sebagai Variabel Intervening Pada Perusahaan Manufaktur - V. Titi Purwantini; Supriyono Supriyono (ProBank, 2018)
The purpose of this studi is to analyze of Factors that affect the Company Value with the Quality of profit as intervening variable on manufacture company on  Manufacturing Companies Listed In Indonesia Stock Exchange. The results obtained as follows: Direct Influence Managerial ownership has a negative and significant effect on Corporate Value, Institutional ownership has a positive and significant effect on Corporate Value, Audit Committee existence has negative and insignificant effect on firm value. Indirect Effect is managerial ownership has a negative and insignificant effect on profit quality as well as earnings quality has positive and significant effect to company value, institutional ownership has negative and insignificant effect on profit quality and earnings quality have positive and significant influence to company value while existence of audit committee influences positive and significant to profitability as well as earnings quality have positive and significant impact to company value. Direct influence Managerial ownership of Corporate Value is greater than the indirect effect of managerial ownership on Corporate Value by mediating the quality of earnings so as to increase the Company's value of the selected direct path. It can be said that earnings quality can not function as intervening variable between managerial ownership and company value. The direct effect of Institutional Ownership on Corporate Value is greater than the indirect effect of Institutional Ownership on Corporate Values with the mediation of earnings quality, so as to increase the Company's value of selected direct paths. It can be said that earnings quality can not function as intervening variable between managerial ownership and company value. The Influence of Audit Committee's Existence on Corporate Value is less than indirect influence The existence of the Audit Committee on Corporate Values with the mediation of earnings quality so as to increase the Company's value is chosen indirect path. It can be said that earnings quality can serve as intervening variable between Audit Committee's existence with company value.                                                                                                                        Keywords: managerial ownership, institutional ownership, presence of audit committee, corporate value, earnings quality